Applications of Reverse Panoramic Radiography for Age and Gender Determination- A Radiographic Study - Karthikeya Patil; Mahima VG; Poornima Chandran; SrishtiTayal; Jaishankar HP (Institute of Medico-legal Publications Pvt Ltd, 2021)
Objectives: This study was conducted to establish if any correlation exists between individual’s chronological age and lambdoid sutures closure status in mortals through modified reverse panoramic radiograph.Materials and Methods: Total number of 140 subjects, 10 years and beyond were included in the study, and divided into seven groups with an age interval of 5 years. Assessment of lambdoid suture closure was done according to Frederic Rating Scale on modified reverse panoramic radiographs. Data obtained was subjected to statistical analysis using Cramer’s V test.Results: A significant correlation was observed between the age group and suture closure. Cramer’s test gave value of 0.000, and was interpreted as a good correlation between the age and suture closure status with a P value of <0.05Conclusion: Lambdoid suture can be very effective and reliable practical tool for age assessment in mortalsthrough modified reverse panoramic radiography (ectocranially)